Reinforcement of PMMA Denture Base Material with a Mixture of ZrO2 Nanoparticles and Glass Fibers - Mohammed M. Gad; Ahmad M. Al-Thobity; Ahmed Rahoma; Reem Abualsaud; Fahad A. Al-Harbi; Sultan Akhtar (Hindawi Limited, 2019)
This study is aimed at evaluating the hybrid reinforcement effects of zirconium oxide nanoparticles (nano-ZrO2) and glass fibers (GFs) at different ratios on the flexural and impact strengths of a polymethylmethacrylate (PMMA) denture base. A total of 160 specimens were fabricated from heat-polymerized acrylic resins using the water bath technique. For the control group, the specimens did not receive any additions; for the test group, different concentrations of nano-ZrO2/GFs at 5% of the PMMA polymer were added. The concentrations of nano-ZrO2/GFs were as follows: 5%-0%, 4%-1%, 3%-2%, 2.5%-2.5%, 2%-3%, 1%-4%, and 0%-5%. The flexural strength was measured using the three-point bending test. The impact strength was measured using the Charpy impact test. Results were tabulated and analyzed using one-way analysis of variance (ANOVA) and the Tukey-Kramer multiple comparison test (p≤0.05). The flexural and impact strengths of PMMA-nano-ZrO2 + GF composites were significantly improved when compared with those of pure PMMA (p<0.05). The maximum flexural strength (94.05 ± 6.95 MPa) and impact strength (3.89 ± 0.46 kJ/m2) were obtained with PMMA (2.5%)/nano-ZrO2 + 2.5% GF mixtures and could be used for removable prosthesis fabrication.